Analisis Produktivitas Mesin Filling Botol 600 Ml dengan Overall Equipment Effectiveness (OEE) - Sholehuddin; Sulistyowati, Enik; Hamidah, Nur (Metode : Jurnal Teknik Industri, 2025)
Dalwa Anugrah Hasaniyah, a manufacturing company, produces bottled drinking water (AMDK). One of the main machines used in the production process is the 600 ml bottle filling machine, which plays a crucial role in ensuring smooth production. However, in actual use, this machine often experiences problems that reduce production efficiency. The most common problems include delays in raw material deliveries, which cause downtime or interruptions in the production process, as well as breakdowns of certain machine components. Decreased productivity and increased production costs are the consequences of this scenario. Using the Overall Equipment Effectiveness (OEE) method, which consists of three main indicators—availability, performance, and quality—this study aims to measure and evaluate the effectiveness of the 600 ml bottle filling machine. Research data was obtained over a period of six consecutive weeks through direct recording of machine operating hours, the number of products produced, defective products, and downtime. The results of data processing indicate that the average OEE value of the filling machine is 78%. This value is still below the world-class OEE standard of 85%. The main factor influencing the low OEE value is the high level of downtime, which significantly impacts the decline in availability, where the average availability value obtained is only 80%. This study concludes that the company needs to implement a scheduled preventive maintenance strategy, increase the reliability of raw material supplies, and optimize operator skills to improve machine effectiveness and approach world-class standards.